The influence of a moderate aerobics programme on the body self-image of women in middle adulthood - Daniels, Andrea K; van Niekerk, Rudolph L (South African Journal of Sports Medicine, 2011)
Objectives. This empirical study investigated the effect of a moderate aerobic exercise programme on the body self-image of a sample of women (n=49) in middle adulthood with a mean age of 54.2 years. Methods. The participants were randomly assigned to an experimental group (n=24) and a control group (n=25). The experimental group participated in a (guided) moderate aerobics programme over six weeks, while the control group participated in a sedentary (guided) meditation programme. The participants in both groups were assessed for body self-image using the nine factors defined in the Body Self-Image Questionnaire (BSIQ) of Rowe (2000). The BSIQ comprises both perceptual-cognitive and affective-attitudinal factors. Results. The results indicated that there was an overall positive shift in the perceptual-cognitive factors of the body self-image in the exercise group, namely for overall appearance evaluation, health fitness evaluation and fatness evaluation. Although no significant shifts were found in all the affective-attitudinal factors of the participants, there was a significant change in the negative affect of the participants. Conclusion. The results suggest that such a programme has a positive influence on the way these women think and feel about their bodies. No significant changes were found in the body selfimage of the control group. These findings suggest the positive effect of a (guided) aerobic exercise programme in improving the body self-image of women in middle adulthood. SAJSM, vol 23 No. 4 2011